A brief remark on the philhellenic policy of Amasis at the emporion Naucratis - Květa Smoláriková (Studia Hercynia, 2022)
The Greek emporia (Al Mina, Naucratis, etc.) were usually founded on the sea shores or in the estuaries of large rivers because they served as important trade routes to the hinterland. Some countries were much more active in the effort of accepting new inventions than others. Thus, no wonder that the further exist ence and prosperity of emporia depended on a wide range of specific local conditions; in the case of Egypt, essentially on the attitude of the king to foreigners. An excellent example is certainly the famous Greek emporion Naucratis and its place in the Egyptian economy under the rule of Amasis (Ahmose II) and his reforms, as were recorded by Herodotus.